Cysteine String Protein Controls Two Routes of Export for Misfolded Huntingtin - Pink, Desmond; Donnelier, Julien; Lewis, John D.; Braun, Janice E. A. (Frontiers in Neuroscience, 2022)
Extracellular vesicles (EVs) are secreted vesicles of diverse size and cargo that are implicated in the cell-to-cell transmission of disease-causing-proteins in several neurodegenerative diseases. Mutant huntingtin, the disease-causing entity in Huntington’s disease, has an expanded polyglutamine track at the N terminus that causes the protein to misfold and form toxic intracellular aggregates. In Huntington’s disease, mutant huntingtin aggregates are transferred between cells by several routes. We have previously identified a cellular pathway that is responsible for the export of mutant huntingtin via extracellular vesicles. Identifying the EV sub-populations that carry misfolded huntingtin cargo is critical to understanding disease progression. In this work we expressed a form of polyglutamine expanded huntingtin (GFP-tagged 72Qhuntingtinexon1) in cells to assess the EVs involved in cellular export. We demonstrate that the molecular chaperone, cysteine string protein (CSPα; DnaJC5), facilitates export of disease-causing-polyglutamine-expanded huntingtin cargo in 180-240nm vesicles as well as larger 10-30m vesicles.